Implementasi Pembelajaran Pendidikan Agama Islam Dalam Pengembangan Aspek Spiritual Anak Berkebutuhan Khusus di Sekolah Dasar Luar Biasa (SDLB) - Amertha, Aurista Sheftia; Anggraini, Fina Surya (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2021)
Learning Islamic Religious Education is a compulsory subject in school institutions that contains the teaching of Islam, which involves students. The purpose of this study is to implement the rights of students with special needs in the realm of education, especially Islamic religious education. The research uses a qualitative approach with the type of case study research. Data analysis techniques include data collection, data presentation, and data verification. The results of the study show that: learning planning uses a learning implementation plan (RPP) and curriculum, learning implementation is carried out once a week, learning evaluation is carried out through assessment which aims to determine the ability level of students with special needs.